2005
DOI: 10.4049/jimmunol.174.3.1507
|View full text |Cite
|
Sign up to set email alerts
|

A20 Is a Negative Regulator of IFN Regulatory Factor 3 Signaling

Abstract: IFN regulatory factor 3 (IRF-3) is a critical transcription factor that regulates an establishment of innate immune status following detection of viral pathogens. Recent studies have revealed that two IκB kinase (IKK)-like kinases, NF-κB-activating kinase/Traf family member-associated NF-κB activator-binding kinase 1 and IKK-i/IKKε, are responsible for activation of IRF-3, but the regulatory mechanism of the IRF-3 signaling pathway has not been fully understood. In this study, we report that IRF-3 activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(143 citation statements)
references
References 39 publications
3
137
1
Order By: Relevance
“…Because A20 is induced by NF-B signaling in a manner similar to IB-␣ resulting in inhibition of NF-B signaling upstream of IB-␣ (59), it is reasonable to speculate that A20 would represent an additional potential target for PKR-dependent translational control of NF-B signaling. Since A20 regulates NEMO activity, and NEMO activity is required for the activation of IRF3 through TBK1 and IK (60), then PKR-dependent inhibition of A20 translation presumably could also affect IRF activation in some instances, perhaps explaining the PKR-dependent activation of IRF3 observed following mutant vaccinia virus infection (32). In fact, the absence of negative regulators of NF-B signaling may also explain the PKR-dependence of IB phosphorylation and activation of IK shown by others (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Because A20 is induced by NF-B signaling in a manner similar to IB-␣ resulting in inhibition of NF-B signaling upstream of IB-␣ (59), it is reasonable to speculate that A20 would represent an additional potential target for PKR-dependent translational control of NF-B signaling. Since A20 regulates NEMO activity, and NEMO activity is required for the activation of IRF3 through TBK1 and IK (60), then PKR-dependent inhibition of A20 translation presumably could also affect IRF activation in some instances, perhaps explaining the PKR-dependent activation of IRF3 observed following mutant vaccinia virus infection (32). In fact, the absence of negative regulators of NF-B signaling may also explain the PKR-dependence of IB phosphorylation and activation of IK shown by others (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we find Traf6 and Tak1 recruited to TLR3, and we find TLR3/4-induced cytokine production ablated in traf6Ϫ/Ϫ cells. Additionally, TLR3 and TLR4 NF-B and IRF-3 responses have been shown to be negatively regulated by the ubiquitin-modifying enzyme A20 (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Hiscott and co-workers (15) showed that virusinduced expression of A20 efficiently blocks RIG-I-mediated activation of NF-B and IRF3 but only weakly interferes with the response initiated by TLR3. On the other hand, two other studies using A20 overexpression or knockdown showed that A20 can also interfere with TLR3-induced IRF and NF-B activation (16,17). These results suggest that virusinducible expression of A20 negatively regulates RIG-I-and TLR3-mediated induction of an antiviral state.…”
Section: Inhibitory Effect Of A20 On Pro-inflammatory Gene Expressionmentioning
confidence: 99%
“…2) (23). Zinc finger 4 is crucial for the ubiquitin ligase activity of A20 (16), but also zinc finger 7 seems to be important for NF-B inhibition (23,38). Some of the zinc fingers in A20 might act as ubiquitin receptors, which is suggested by the observation that Rabex-5 is able to directly bind ubiquitin via an A20-like zinc finger motif (39).…”
Section: Molecular Mechanism Of A20 Activitymentioning
confidence: 99%